Structural investigation of lipopolysaccharides from nontypeable Haemophilus influenzae: investigation of inner-core phosphoethanolamine addition in NTHi strain 981. - Tinnert, A; Månsson, M; Yildirim, H; Hood, D; Schweda, E (2005)
LPS of NTHi comprises a conserved tri-l-glycero-D-manno-heptosyl inner-core moiety (l-alpha-D-Hepp-(1-->2)-[PEtn-->6]-l-alpha-D-Hepp-(1-->3)-[beta-D-Glcp-(1-->4)]-l-alpha-D-Hepp-(1-->5)-alpha-Kdop) in which addition of PEtn to the central heptose (HepII) in strain Rd is controlled by the gene lpt6. It was recently shown that NTHi strain 981 contains an additional PEtn linked to O-3 of the terminal heptose of the inner-core moiety (HepIII). In order to establish whether lpt6 is also involved in adding PEtn to HepIII, lpt6 in strain 981 was inactivated. The structure of the LPS of the resulting mutant strain 98llpt6 was investigated by MS and NMR techniques by which it was confirmed that the lpt6 gene product is responsible for addition of PEtn to O-6 of HepII in strain 981. However, it is not responsible for adding PEtn to O-3 of HepIII since the 981lpt6 mutant still had full substitution with PEtn at HepIII.